The contractual infringement and damages to Municipal Public Administration (Research, Society and Development, 2021)
The purpose of this article is to analyze the problem of contractual management and the damage that contractual interference brings to the municipal public administration.  The perfect management of public administration contracts minimizes problems and eventual failures in performance and delivery. This perfection of management essentially involves a firm contract for performance and a delegation of responsibility to other public agents, which means that the chosen one has a particular responsibility, namely the absolute verification of the contract's performance. In order for such issues to be spared, it is admirable that the contractual management takes place in a prudent and responsible manner. It can also be said that probity must govern the entire life cycle of the contract. The article also deals with the responsibility of the public manager, since he has the right to delegate an administrative act, he continues to be bound by the responsibility for that which has been delegated. The manager has the obligation to make a good choice when appointing the contract inspector, in the sense that by delegating unprepared employees, the public manager will be assuming the risks that may arise from a bad choice.  In addition to responsibly appointing the manager, the public agent must offer training so that the management, if any, can be done in an improved manner. Furthermore, the contract manager/fiscal must be aware that, due to his legal attributions, he has the competence to manage and decide, which makes him responsible for that administered object, so he must manage it properly so that the consequences of the Law do not fall upon him.